2020
DOI: 10.1002/vms3.306
|View full text |Cite
|
Sign up to set email alerts
|

High‐energy diet improves growth performance, meat quality and gene expression related to intramuscular fat deposition in finishing yaks raised by barn feeding

Abstract: This research aimed to investigate the effects of dietary energy concentration (combined net energy, Nemf) on growth performance and meat quality of yaks raised by barn feeding. In all, 30 male yaks (3‐year old and 114.57 ± 21.56 kg of body weight) were allocated to one of three isonitrogenous dietary treatments that had different Nemf concentrations (low 3.72 MJ/kg, middle 4.52 MJ/kg and high 5.32 MJ/kg, respectively). The yaks were fed for 120 days. The results showed that the final weight, average daily gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
(55 reference statements)
6
11
1
Order By: Relevance
“…Cooking loss and water holding capacity are important factors in evaluating the meat quality, which affect the juiciness of cooked meat ( 39 ). In the present study, the significant decreasing trend of cooking loss and water loss were observed with increasing dietary energy levels, which is consistent with the study of Kang et al ( 6 ). Shear force is an important indicator of meat tenderness.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Cooking loss and water holding capacity are important factors in evaluating the meat quality, which affect the juiciness of cooked meat ( 39 ). In the present study, the significant decreasing trend of cooking loss and water loss were observed with increasing dietary energy levels, which is consistent with the study of Kang et al ( 6 ). Shear force is an important indicator of meat tenderness.…”
Section: Discussionsupporting
confidence: 93%
“…meat (39). In the present study, the significant decreasing trend of cooking loss and water loss were observed with increasing dietary energy levels, which is consistent with the study of Kang et al (6). Shear force is an important indicator of meat tenderness.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Petri et al [ 9 ] reported that the fatty acid profile in subcutaneous fat is related to rumen bacterial community composition. Our previous study showed that high dietary energy level significantly increased the longissimus dorsi intramuscular fat content, increased the polyunsaturated fatty acid (PUFA) content, and decreased the saturated fatty acid (SFA) content in the intramuscular fat of fattening yaks [ 10 ]. The intramuscular fat fatty acid profile is important for meat quality and human health; however, there is little information available about the correlativity between rumen bacterial populations and intramuscular fat fatty acid profiles in fattening yaks.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, improvement of the meat quality of Sunit sheep is vital and urgent. Kang et al ( 3 ) found that the deposition of intramuscular fat could improve the tenderness and water retention of meat. Nemati et al ( 4 ) discovered that vitamin E increased the antioxidant capacity of meat, which improved meat quality.…”
Section: Introductionmentioning
confidence: 99%